Analisis dan Evaluasi User Interface Design untuk Usability menggunakan Metode Heuristic Evaluation pada Web Perusahaan Bioteknologi - Sella Rabila; Sirojul Munir; Tifanny Nabarian; Davied Wismanindra (Jurnal Informatika Terpadu, 2022)
A website must meet the needs of its users. Of course, when users access a website, they are sure to find the information they are looking for. For this reason, it is necessary to pay attention to the web page that meets the needs of its users. In paying attention to this, an evaluation of the usability of the user interfaces on the website of PT. Enzym Biotechnology Internusa with feedback provided by users based on their experiences when interacting with the website. It is hoped that with this test, the results of the usability of the user interface design on the website using the Heuristics Evaluation method can be known, and the results of the analysis can determine the effect of effectiveness, efficiency, and quality of information experienced by users on the website. The test method uses Heuristics Evaluation, with a sample of ordinary users and users who usually access the website; data collection is done using a questionnaire. The results obtained from this study showed that respondents agreed that the overall Heuristics aspect was quite good, the website's usability was relatively easy to understand, the display met user expectations, and the information provided was entirely in line with reality.